Koda’s Fasting Therapy: Energy Balance and Intestinal Bacterial Flora - Azusa Hirakawa; Shaw Watanabe; Shigeho Tanaka (Advances in Food Technology and Nutrition Sciences, 2015)
Since ancient times, fasting has been performed for religious reasons or as a cure of illnesses. Mitsuo Koda developed fasting dietary therapy and confirmed beneficial effects for many patients with intractable diseases. About 900-1000 kcal/day by unpolished brown rice, green vegetable paste and tofu constitute the basic regimen of Koda’s therapy. This case report deals with women patient (M) who had suffered spino-cerebellar degeneration at a young age and recovered by using Koda’s method. She had been living on only one glass of fresh veg-etable juice per day for 19 years since her acute episode at age 20. Four other persons who were experimenting Koda’s method were asked to join the study for comparison. In our case series, the Basic Metabolic Rate (BMR) was 1000-1200 kcal, which was equivalent with the intake, but in case of M the nutritional intake was almost one tenth of others. M’s ketone bodies, especially β-Hydoxy Butyrate (BHB) in the blood, were more than 3 mM, so the main energy should come from ketone bodies. Biochemical changes of M coincided with the metabolic adaptation to yield BHB, as shown by elevated Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Creatine Kinase (CK). High aspartate was a reflection of above metabolic change. Increased BHB was observed in two participants, M and H, and both of them had Bifidobacteriacae in fecal bacteria. Energy balance and biochemical changes were discussed in these five subjects with calorie restriction.